ANALYSIS OF EXPENDITURE PERFORMANCE IN THE BUDGET REALIZATION REPORT IN BATUKUDA VILLAGE, MANCAK DISTRICT, SERANG REGENCY - Sari, Gema Ika; Hidayatullah, Hidayatullah; Elly K.N, Nabila (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to determine the expenditure performance in the budget realization report in Batukuda Village, Mancak District, Serang Regency, for the 2017-2020 fiscal year using an analysis of spending variance, spending growth, shopping compatibility analysis, and spending efficiency analysis. The analytical method used in this research is descriptive quantitative. Based on what has been done, a) Expenditure performance in terms of expenditure variance analysis is good because the realization of expenditure is smaller than the budget, except for 2017. After all, it exceeds the specified criteria. b) Expenditure performance in expenditure growth analysis cannot be said. Positive because in 2018 and 2020 there was a decrease in spending or negative results, c) Expenditure performance in terms of the compatibility analysis of expenditure was more dominant than capital expenditure compared to operating expenditure of 50.74% and 41.62%, capital expenditure received the criteria not balanced with the proportion of 5-20%, while operating expenditures had an unbalanced criterion with a proportion of 60-90%, d) Expenditure performance in terms of the expenditure efficiency ratio can be said to be efficient because the criteria are below 100% except for 2017.